2020
DOI: 10.5194/acp-20-10953-2020
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer and highly oxygenated organic molecule formation from oxidation of oxygenated monoterpenes emitted by California sage plants

Abstract: Abstract. Plants emit a diverse range of biogenic volatile organic compounds (BVOCs) whose oxidation leads to secondary organic aerosol (SOA) formation. The majority of studies of biogenic SOA have focused on single or simple multicomponent BVOC mixtures thought to be representative of Northern hemispheric deciduous or mixed forest conditions. Gaps remain in our understanding of SOA formation from complex mixtures of real plant emissions in other environments. Towards the goal of understanding SOA in other reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The detected products are all highly oxygenated compounds with a molecular mass that is often higher than that of ACS, which can have implications for SOA formation processes. Indeed, it has been shown that highly oxygenated compounds in the gas phase contribute to the formation of SOA, in particular, by participating in the growth of new particles. , …”
Section: Resultsmentioning
confidence: 99%
“…The detected products are all highly oxygenated compounds with a molecular mass that is often higher than that of ACS, which can have implications for SOA formation processes. Indeed, it has been shown that highly oxygenated compounds in the gas phase contribute to the formation of SOA, in particular, by participating in the growth of new particles. , …”
Section: Resultsmentioning
confidence: 99%
“…This explanation matches our finding that the contribution of the LMW fraction to total BrC absorption is lower at higher peat moisture contents (Figure c). Lower combustion temperatures are also associated with decreased emission of highly oxygenated species, which are important for the secondary formation of high-molecular-weight (HMW) species; ,, this could also account for the smaller absorption contributions from LMW chromophores at higher peat moisture contents.…”
Section: Results and Discussionmentioning
confidence: 99%
“…While SOA production due to monoterpene ozonolysis has been well studied, ,, comparatively less is known with regard to monoterpenoid ozonolysis. A few studies have observed SOA production due to the ozonolysis of C 10 H 16 O and C 10 H 18 O isomers, , while C 10 H 14 O and C 10 H 20 O isomers have not yet been evaluated. In addition to HOMs produced by the ozonolysis of monoterpenes and monoterpenoids, it is likely that human-emitted ammonia (NH 3 ) , (via the researcher applying the disinfectant) and outdoor-to-indoor transported sulfuric acid (H 2 SO 4 ) (via the powered ventilator) participated in the initial steps of particle nucleation and growth.…”
Section: Resultsmentioning
confidence: 99%